An Overview of Mexico’s System of Legal Education - Luis Fernando Pérez Hurtado (My University, 2016)
A recent study in Mexico by the United Nations Human Rights Commission found that the lack of structure regarding the training in and practice of law in Mexico has been a cause of the country’s problems with administering justice and human rights violations. In light of this study, this article explores the process of obtaining a license to practice law, the content and structure of existing law degree programs, and the recent increase in such programs.